SERVICES EXPORT PROMOTION, A PRIORITY WITHIN THE GLOBAL WORLD ECONOMY - OCTAVIAN-LIVIU OLARU (Challenges of the Knowledge Society)
The basic challenge in exporting a service is to convince a foreigner to try a service that does not exist yet. The foreigners have to believe that the service will be of good quality and will meet their needs. Usually the foreigner forms that belief based on recommendations, referrals, or somehow seeing the service provider in action. There are also several roles that trade promotion activities can play in building that belief or credibility. A national TPO needs to find or reinforce some special quality that its country has so that when potential customers hear about a service supplier from this country, their first response is, “Oh yes, I’ve heard good things about services from your country.”